Using Augmented Reality (AR) to Create Place-Based Language Learning Tasks in the Historic Old Town of Jakarta - Yang Xiang; Li Na; Sun Wei; Rustiyana Rustiyana (International Journal of Language and Ubiquitous Learning, 2025)
Background. Place-based learning has gained increasing attention in language education for its ability to situate meaning-making within authentic sociocultural environments. In Indonesia, the Historic Old Town of Jakarta (Kota Tua) represents a rich linguistic and cultural landscape that remains underutilized as a pedagogical resource for contextualized language learning. Purpose. This study explores the use of AR to design and implement place-based language learning activities that enhance learners’ engagement, vocabulary acquisition, and cultural awareness. Method. Employing a design-based research approach, the study involved 42 university students who completed AR-mediated tasks across selected historical landmarks. Data were collected through pre- and post-tests, field observations, and semi-structured interviews. Results. The findings indicate that AR significantly increased learner engagement, facilitated more meaningful vocabulary retention, and encouraged students to make connections between linguistic input and the cultural narratives of Kota Tua. Conclusion. The study concludes that AR-enhanced place-based tasks offer a promising pedagogical model for integrating digital technologies with experiential learning in heritage settings. Further research is recommended to explore scalability, long-term learning effects, and cross-cultural applicability.